Effect of Social Assistance Programmes on Improving Quality of Life in Kenya: Evidence from Machakos County - Ngelu, Joshua Mutambu (European Scientific Journal, ESJ, 2017)
This study investigates the effect of social assistance programmes on improving quality of life in Kenya - evidence from Machakos County. Probit model was applied to model the empirical analysis. The paper concludes that moderate households’ awareness of available types of cash transfer. On the households’ quality of life with reference to social assistance programmes, the study posits that households in receipt of bursary support, cash transfers for orphans and vulnerable children, and cash transfers to the elderly will report an improved life quality compared to their counterparts who have not received such transfers. Similar conclusion is arrived at for remittances receipts from relatives residing outside the County. The paper recommends application and scaling up of social assistance programmes to reduce poverty at county and national levels so that in turn can improve quality of life of households. This will go a long way in achieving the Sustainable Development Goals.